Nilai-Nilai Zuhud dalam Tafsir al-Mishbah dan Relevansinya terhadap Fenomena FOMO pada Generasi Muda - Nur Syahvika; Nurdiani Nurdiani; Indra Suardi (ALSYS, 2026)
Although studies on zuhud based on Tafsir al-Mishbah have received attention in a number of previous studies, discussions that specifically examine its relevance to the FOMO phenomenon among young people remain limited. This study aims to analyze the relevance of the values of zuhud in the verses of the Qur’an to the FOMO phenomenon among young people in the digital era. This study used a qualitative approach with a library research design through a thematic exegesis (maudhu’i) approach. The research data sources included primary and secondary data, which were collected through documentation techniques, literature study, as well as searches of digital databases and scientific journals. The data were analyzed using content analysis, while the validity and credibility of the data were maintained through source triangulation and theory triangulation. The results showed that the values of zuhud in Tafsir al-Mishbah have very strong relevance as a spiritual-psychological solution for those experiencing FOMO. This finding contributes to the development of studies on the FOMO phenomenon among young people while also expanding understanding of the concept of zuhud in Tafsir al-Mishbah. The conclusion of the study emphasizes that zuhud can build the mental resilience of young people so that they remain able to interact wisely in the digital era without losing their identity. The implications of this study include a theoretical contribution in enriching the literature on the relevance of the values of zuhud as a spiritual-psychological solution to FOMO, as well as practical implications for young people and educators. This study also opens opportunities for further research on the implementation of the values of zuhud in preventing the negative impacts of the FOMO phenomenon.